Preliminary evaluation of a microtransesophageal probe in neonates and young infants undergoing surgery for congenital heart disease - Sreeja Pavithran; Kanagarajan Natarajan; Bijesh Vishwambaran; Avinash Dayalal Arke; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2014)
Background: The larger size of the currently available transesophageal echocardiography (TEE) probes limits their use to relatively older infants undergoing cardiac surgery. In very young neonates and infants, epicardial echocardiogram is used to assess postoperative residual defects. Recently, a miniaturized microTEE probe compatible in neonates has been introduced for clinical use. We evaluated the use of this probe in small infants undergoing cardiac surgery. Materials and Methods: Thirty-three consecutive neonates and infants undergoing cardiac surgery at our institution were included in the study. Intraoperative echocardiography with Philips s8-3t microTEE probe done using IE33 platform was utilized to study the preoperative anatomy and assess postoperative results. Results: Thirty-three patients aged 3 days-2 years (mean 5.1 months) and weighing 2.5-11 kg (mean 4.4 kg) underwent perioperative evaluation using the microTEE probe. Good quality two-dimensional and color Doppler images were obtained in all patients. There were no complications related to the probe insertion or manipulation. The findings on microTEE led to revision of surgery in five patients. Certain echocardiographic parameters that could never be recorded with epicardial echocardiogram could be easily seen in microTEE. Conclusion: On preliminary evaluation, the microTEE probe provided good quality images in very small infants who were not amenable for transesophageal echocardiographic evaluation so far. The probe could be used safely in small infants without complications. It appears to be a promising imaging modality in the perioperative assessment of young infants undergoing cardiac surgery, in whom intraoperative epicardial echocardiography is currently the only tool.